Response Mechanism of Endogenous Hormones of Potential Storage Root to Phosphorus and Its Relationship With Yield and Appearance Quality of Sweetpotato - Si, Cheng-cheng; Liang, Qing-gan; Liu, Hong-Juan; Wang, Ning; Kumar, Sunjeet; Chen, Yan-li; Zhu, Guo-peng (Frontiers in Plant Science, 2022)
Field and pot experiments were conducted to explore the response mechanism of endogenous hormones of potential storage root to phosphorus and its relationship with yield and appearance quality of sweetpotato using five different rates of phosphorus addition. Application of adequate amounts of phosphorus (P2 treatment, 112 kg of P2O5 ha–1 in field experiment or 0.04 g of P2O5 kg–1 in pot experiment) improved the yield and the appearance quality of sweetpotato when compared to the control treatment. This observation can be attributed to the fact that P2 treatment significantly increased the expression of Ibkn1 and APRT genes and the concentration of ZR from 20 to 40 days after planting, but the results were the opposite at 10 days after planting. In addition, an increase in the expression of SRD1, NIT4, IbMADS1, and OPR3 and the concentrations of IAA and JA from day 10 to day 40 after planting were observed. Furthermore, the expression of GA3oX4 and the concentration of GA3 decreased significantly from 20 to 30 days of planting and significantly increased after 40 days of planting. Moreover, a significant decrease in the expression of AAO and concentration of ABA was observed from 10 to 30 days after planting, and a significant increase was observed after 40 days of planting. The results show that P2 treatment promoted root development, particularly significantly increased the number of roots and potential storage roots. P2 treatment significantly increased the diameter, weight, and number of storage roots at 40 days after planting. Finally, proper phosphorus application (112 kg of P2O5 ha–1) increased the yield (enhanced from 18.99 to 25.93%) by increasing the number of storage roots per plant and improving the appearance quality by increasing the length/diameter ratio and uniformity of storage root weight.